How to manage experience sharing : from organisational surprises to organisational knowledge - Andriessen, J. H. Erik; Fahlbruch, Babette (Elsevier, 2004)
Combining the experiences of safety science and knowledge management in service organisations, this book focuses on individual and group processes and on organisational strategy or societal and environmental issues. It addresses questions such as how can an organisation learn from its successes and failures, from its experiences and accidents.